Tauroursodeoxycholic acid (TUDCA) abolishes chronic high salt‐induced renal injury and inflammation. (23rd December 2018) - De Miguel, Carmen; Sedaka, Randee; Kasztan, Malgorzata; Lever, Jeremie M.; Sonnenberger, Michelle; Abad, Andrew; Jin, Chunhua; Carmines, Pamela K.; Pollock, David M.; Pollock, Jennifer S.
Abstract: Aim: Chronic high salt intake exaggerates renal injury and inflammation, especially with the loss of functional ETB receptors. Tauroursodeoxycholic acid (TUDCA) is a chemical chaperone and bile salt that is approved for the treatment of hepatic diseases. Our aim was to determine whether TUDCA is reno‐protective in a model of ETB receptor deficiency with chronic high salt‐induced renal injury and inflammation. Methods: ETB ‐deficient and transgenic control rats were placed on normal (0.8% NaCl) or high salt (8% NaCl) diet for 3 weeks, receiving TUDCA (400 mg/kg/d; ip) or vehicle. Histological and biochemical markers of kidney injury, renal cell death and renal inflammation were assessed. Results: In ETB ‐deficient rats, high salt diet significantly increased glomerular and proximal tubular histological injury, proteinuria, albuminuria, excretion of tubular injury markers KIM‐1 and NGAL, renal cortical cell death and renal CD4 + T cell numbers. TUDCA treatment increased proximal tubule megalin expression as well as prevented high salt diet‐induced glomerular and tubular damage in ETB ‐deficient rats, as indicated by reduced kidney injury markers, decreased glomerular permeability and proximal tubule brush border restoration, as well as reduced renal inflammation. However, TUDCA had no significant effect on blood pressure. Conclusions: TUDCA protects against the development of glomerular and proximal tubular damage, decreases renal cell death and inflammation in the renal cortex in rats with ETB receptor dysfunction on a chronic high salt diet. These results highlight the potential use of TUDCA as a preventive tool against chronic high salt induced renal damage.